Annual reproductive cycle and growth of the pen shell Atrina maura (Pterioidea: Pinnidae) on sand-bottom culture in the Ensenada Pabellones lagoon system, Gulf of California, Mexico. Issue 1 (2nd January 2016) - Gongora-Gomez, Andres; Garcia-Ulloa, Manuel; Arellano-Martínez, Marcial; Abad, Selene; Dominguez, Ana; Ponce-Palafox, Jesus
Abstract: The reproductive cycle and growth of the pen shell, Atrina maura, which was cultured in the Ensenada Pabellones lagoon system, Gulf of California, from March 2008 to March 2009, is described in this article. Histological techniques and the condition index were used to determine its reproductive condition. The sex ratio was 0.57 females:1.72 males within the population studied. There were no differences ( χ 2, p < 0.05) in shell length (SL) between males and females. The mean length of the sampled specimens ranged between 50.99 ± 4.86 mm and 218.16 ± 8.87 mm. The histological results confirmed that A. maura is a gonochoristic organism that presents synchronic development of the gonads. The maturity and spawning phases were observed throughout the study period, with the exception of March and May 2008. The frequency of the gonad development stages obtained per month suggests that this species reproduced two times annually, with one important reproductive period from June to September, a minor reproductive period from November to February, and two resting periods as follows: July to August and January to February 2009.